Electrooptic proprieties of layer-by-layer films of a azobenzene containing copolymer - Ribeiro, Paulo A. (2005)
The methacrylic copolymer functionalized with the azo chromophore 4-[N-ethyl-N-(2-hydroxiethyl)]-amino-2′-chloro-4-nitroazobenzene (MMADR13), in its polyelectrolyte form, can be used to fabricate thin films by the layer-by-layer (LbL) technique just if one alternates this anionic polyelectrolyte with a cationic polyelectrolyte such as poly(allylamine hydrochloride) (PAH). Since PAH does not present any particular optical functionality, the main final film feature will came from the side chain DR13 azo-chromophore group due to its large nonlinear optical properties and photoisomerization capabilities. This work reports the electrooptic activity of MMADR13/DR13 LBL films, which arises from the high hiperpolarizability about the azo side chain group.